Development of Online-Based Digital Learning Media for Geography Subjects at Madrasah Aliyah Negeri I Wonosobo - Farida Ariani; G.A. Ghansyam (Teknodika, 2022)
Nowadays, learning media is growing in line with the rapid development of information technology. This research was conducted in connection with the need for learning media that can be used anywhere and anytime without any limitation of place and time. This study aims to develop online learning media products for geography learning. The research method used was the Research and Development (R&D) method. The research subjects were students of class X Madrasah Aliyah Negeri 1 Wonosobo. Data collection techniques used the methods of observation, interviews, questionnaires, and documentation. Questionnaires were employed to determine the feasibility of online-based learning media, whereas data analysis techniques utilized percentage techniques. From the study results, it can be concluded that the online-based learning media developed can be said to be good by experts. It can be seen from the testing results on students to determine the level of media feasibility based on predetermined criteria/indicators. Thus, this learning media deserves to be used as an alternative learning media with a good category (88%), namely with details on educational criteria with good results (93%), appearance criteria with good results (85%), and technical criteria with good results (89%). Hence, online-based learning media for geography class X is feasible to use as a choice of digital learning media.